(untitled) (SAARC Journal of Agriculture, 2018)
A study was carried out to study the effect of freezing on cryosurvival of yak semen. Artificial insemination in yak is still in infancy. Semen cryopreservation and use of artificial insemination can be applied in yak husbandry for conservation and rapid multiplication of superior germplasm. Semen was collected from four adult yak bulls using artificial vagina method managed under uniform conditions. A total of 40 ejaculates comprising of 10 ejaculates each bull were collected following twice a week schedule and evaluated for fresh semen characteristics. The fresh yak semen characteristics viz. ejaculate volume (ml), mass activity (0-4), initial sperm motility (%), sperm concentration (x 106/ml), live sperm (%), sperm abnormality (%) and intact acrosome (%) were 3.10 ± 0.18, 3.53 ± 0.96, 83.89 ± 2.87, 1180.22 ± 42.32, 77.63 ± 4.23, 8.45 ± 3.33 and 93.61 ± 3.78 respectively. The ejaculates were diluted (1:10) with Tris extender consisting of 6.4 ml glycerol and 20 ml of fresh egg yolk. Straws were equilibrated at 5°C for 4 hours followed by exposure to liquid nitrogen vapour for 10 minutes and finally transferred to liquid nitrogen container for storage. The cryosurvival rate was studied after 7 days of storage in liquid nitrogen. The frozen semen was thawed in warm water (37°C) for 30 seconds for evaluation. Mean values of postthaw sperm motility (%), live sperm (%) and intact acrosome (%) in yaks were 55.67 ± 4.67, 65.62 ± 3.23 and 89.26 ± 3.67 respectively. In conclusion, yak semen has a better cryosurvival while freezing in tris extender with 6.4 per cent glycerol and 20 per cent egg yolk following an equilibration period of 4h. SAARC J. Agri., 15(2): 215-218 (2017)